The Effectiveness of Facebook Group Discussions on Writing Performance: A Study in Matriculation College - Ng Sau Ping; Mahendran Maniam (International Journal of Evaluation and Research in Education (IJERE), 2015)
Matriculation a pre-tertiary program offered by Ministry of Education for students who have completed their ‘Sijil Pelajaran Malaysia’s’ (SPM) examinations successfully. These excellent students will be required to sit for the Malaysian University English Test (MUET) before pursuing their studies in local colleges and universities. MUET comprises all the four language skills of listening, speaking, reading and writing. However, matriculation students are still unable to perform well in MUET examination especially the writing component. Researcher aimed to see whether Facebook group discussions can be used as a medium to improve writing skills of students. The main purpose of this study is to look at the effectiveness of Facebook group discussion in writing performance and college students’ perception of using Facebook discussion. This study tested the effect of Facebook discussions by comparing 2 groups of learners (a control group and an experimental group) on writing tasks. The scores of Pre and Post test for both groups will be compared after treatment method of Facebook group discussion on the experimental group. Learners’ attitudes towards the usage of Facebook group discussion and aspects of Facebook that help students to express their opinion. Discussions of the findings will include suggestions on whether Facebook discussions can be used to improve writing performance.